1974
DOI: 10.1122/1.549327
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State and Oscillatory Flow Properties of Polymer Solutions

Abstract: Viscosities, first and second normal-stress differences, and related material functions were determined for steady-state and oscillatory shearing of polyethylene oxide and polyacrylamide solutions by use of a Weissenberg R-17 Rheogoniometer with cone-and-plate shearing geometry. Pressure transducers—located along the radius of the plate, with their 0.04-in-O.D. pressure-sensing membranes flush with the plate surface—were used to determine local values of the normal stress. The sensitivity of the transducers wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1974
1974
2001
2001

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…This prediction is of great importance because there is still confusion concerning the sign of N 2 of polymer solutions and melts (7)(8)(9)(10)(11).…”
Section: *mentioning
confidence: 97%
“…This prediction is of great importance because there is still confusion concerning the sign of N 2 of polymer solutions and melts (7)(8)(9)(10)(11).…”
Section: *mentioning
confidence: 97%
“…It is possible, for a very great variety of polymeric materials, to use a power-law expression for correlating the primary normal-stress difference as a function of shear stress [12]. At the same time, the assumption of a constant ratio, e, of the secondary and the primary normal-stress differences is reasonable in the light of the few reliable experimental data available in the literature [13][14][15]. Therefore, it can be shown that the nu-term is proportional to the so-called recoverable shear, SR, or the Weissenberg number, We (of Deborah number, De, for some numerical works).…”
Section: Z Wmentioning
confidence: 99%
“…Comparison with experimental data will be performed with four polymeric solutions: a 2.5% solution of polyacrylamide in a 50% water and 50% glycerine solution (PAA) [41], a 1.1% polyisobutylene solution in decahydronaphthalene (Oppanol B200) [42], a 3% solution of polyethylene oxide in a 57%-water, 38%-glycerine and 5%-isopropyl-alcohol solution (PEO) [41,42], and a 8.7% polyisobutylenedecalin solution "D2b" (Oppanol BS0) [43]. (49) The reason for chosing the PAA and PEO solutions is that, in these cases, all three viscometric functions r/, ~, and ¢/2 have been determined experimentally (50) and that concomitantly, data concerning oscillatory shearing are also available.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%